2020
DOI: 10.1101/2020.07.19.210781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaze dynamics of feature-based distractor inhibition under the prior-knowledge and expectation

Abstract: Prior information about distractor facilitates selective attention to task-relevant items and helps the optimization of oculomotor planning. Particularly, feature-based attentional inhibition could be benefited from the pre-knowledge of critical features of the distractors. In the present study, we capitalized on gaze-position decoding to examine the dynamics of attentional deployment in a feature-based attentional task that involved two groups of dots (target/distractor dots) moving toward different direction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…This might account for the very early (,100 ms) emergence of the template information extracted by decoding. In fact, previous work showed that expectation could preactivate representations of expected sensory stimuli (Kok et al, 2017) and strategically bias gazes toward the foreknown distractor in the preparatory stage to reduce stimulus-evoked attractions (Wen et al, 2021). Behaviorally, fixed cues also facilitate distractor suppression, which echoed previous findings that participants can be more effective in excluding the irrelevant items in a predictive context (Töllner et al, 2015;Cunningham and Egeth, 2016;Noonan et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…This might account for the very early (,100 ms) emergence of the template information extracted by decoding. In fact, previous work showed that expectation could preactivate representations of expected sensory stimuli (Kok et al, 2017) and strategically bias gazes toward the foreknown distractor in the preparatory stage to reduce stimulus-evoked attractions (Wen et al, 2021). Behaviorally, fixed cues also facilitate distractor suppression, which echoed previous findings that participants can be more effective in excluding the irrelevant items in a predictive context (Töllner et al, 2015;Cunningham and Egeth, 2016;Noonan et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…This might account for the very early (<100 ms) emergence of the template information extracted by decoding. In fact, previous work showed that expectation could pre-activate representations of expected sensory stimuli 48 and strategically bias gazes toward the foreknown distractor in the preparatory stage to reduce stimulus-evoked attractions 49 . Behaviorally, fixed cues also facilitate distractor suppression which echoed previous findings that participants can be more effective in excluding the irrelevant items in a predictive context 14,17,20 .…”
Section: Discussionmentioning
confidence: 99%